Development of empty fruit bunch filter with addition of chitosan for pre-treament of palm oil mill effluent - Mohd, M. G.; Othman, N.; Sadikin, A. N.; Khalid, S. S.; Yusof, N. (Faculty of Chemical Engineering & Natural Resources, 2008)
The separation performance of empty fruit bunch (EFB) filters with addition of chitosan on the pre-treatment of palm oil mill effluent (POME) has been investigated. Chitosan is an adsorbent which has been used widely in the wastewater treatment. A relatively EFB filters with various concentration of chitosan added and different length of fibers were prepared in order to find the most efficient filter. The performance was assessed in terms of chemical oxygen demand (COD), pH and total suspended solids (TSS) reduction. The results obtained showed that the percentage of reduction of the COD, pH and TSS increased as the concentration of chitosan increased and the length of the fibers shorter. The filter made of 6mm fibers and mixed with 4wt% of chitosan yielded the highest percentage of COD, pH and TSS reduction of25.92%, 26.05 and 49.19% respectively.